2012
DOI: 10.1111/j.1365-2109.2012.03258.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between prey utilization and growth variation in hatchery-reared Pacific bluefin tuna,Thunnus orientalis(Temminck et Schlegel), larvae estimated using nitrogen stable isotope analysis

Abstract: In mass culture of Pacific bluefin tuna Thunnus orientalis, a marked growth variation is observed after they start feeding at 6-7 mm in body length (BL) on yolk-sac larvae of other species, and the growth variation in tuna larvae is a factor leading to the prevalence of cannibalism. To examine the relationship between prey utilization and growth variation, nitrogen stable isotope ratios (d 15 N) of individual larvae were analysed. A prey switch experiment was conducted under two different feeding regimes: a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…ABFT larvae are fast-growing, showing a rapid development of internal organs, including that of the digestive system (Miyashita et al 2001, Kaji 2003, Yúfera et al 2014. Considering the high nutritional requirements for developing fast developmental rates, some authors have suggested that the feeding shift from a planktivorous to a piscivorous diet is particularly important for survival in this species (Tanaka et al 2014, Reglero et al 2014.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…ABFT larvae are fast-growing, showing a rapid development of internal organs, including that of the digestive system (Miyashita et al 2001, Kaji 2003, Yúfera et al 2014. Considering the high nutritional requirements for developing fast developmental rates, some authors have suggested that the feeding shift from a planktivorous to a piscivorous diet is particularly important for survival in this species (Tanaka et al 2014, Reglero et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…SIA has proven to be a potential tool to study trophic ecology of wild-caught fish larvae (Laiz-Carrión et al 2011, Quintanilla et al 2015. But field research still needs experimental proof to understand the patterns of ontogenic-related feeding shifts and isotopic variations (Gamboa-Delgado et al 2008, Varela et al 2011, Tanaka et al 2014.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of a feeding experiment on larvae of the Pacific blue fin tuna (Thunnus orientalis) showed that nitrogen values of fish approximated the isotopic composition of the food source after 20 days (Tanaka et al 2014). In other experiments on larvae of the catfish Clarias gariepinus and Ictalurus punctatus, results of isotopic compositions reached the "plateau" phase between 4 to 10 weeks, respectively (Enyidi et al 2013, Filbrun andCulver 2014).…”
Section: Unreached Isotopic Equilibrium After 24 Days Post-settlementmentioning
confidence: 99%